Sujeito contemporâneo, conhecimento e barbárie: uma leitura a partir da dialética negativa, de Theodor Adorno - Werlang, Julio Cesar (Universidade do Vale do Rio dos Sinos, 2015)
Critical reflection on the subject and subjectivity in the contemporary context from the thought of Theodor Adorno, specifically in its negative dialectic with the focus on the question of knowledge and barbarism. The primacy of the object as indicative of a new epistemological conception, required to open real emancipatory possibilities of the subject in the administered world. The critical and conscious subject of its determinations, limits and possibilities in late capitalist societies, presents itself as one cultivates his inner self and individuality as opposed a self referentialityand the individualism of liberal subject, and maintains a contemplative, reflective and resilient look in winning its freedom in the midst of false freedom promoted by the culture industry, being ethically sensitive and supportive with the pain and suffering of others and of nature, and thus becomes an artist and protagonist of a new time.
Keywords: Adorno; Dialética negativa; Sujeito liberal e sujeito crítico; Subjetividade; Primado do objeto; Conhecimento e barbárie; Experiência emancipação; Interioridade e individualidade; Particular e universal; Sensibilidade ética; Olhar meditativo; Reflexivo e resistente; Artista e protagonista; Negative dialectic; Liberal and critical subject; Primacy of the object; Subjectivity; Knowledge and barbarism; Emancipation; Inner self and individuality; Contemplative; Reflective and resilient look; Ethically sensitive; Artist and protagonist; ACCNPQ::Ciências Humanas::Filosofia